Boosting teacher quality: pathways to effective policies - Halász, Gábor; Looney, Janet; Michel, Alain; Sliwka, Anne (Publications Office of the European Union, 2018)
This study gathers evidence on policies that aim to raise students' learning outcomes through incentives and support measures to enhance teacher quality. A central concern is to identify policies that are effective and efficient. These include incentives and support systems to ensure that high-quality candidates are recruited to initial teacher education, retained and supported to develop and deepen their professional competences (both individual and collective) throughout their careers. This focus on effectiveness and efficiency is particularly important in the context of increasing demands on teachers and stricter limits on education spending. This study explores eight key policy areas to support, develop and incentivise teacher quality, and over time, to deepen professionalism. They include two transversal and six specific policy instruments or measures that are part of a general policy mix to support individual and collective teacher professionalism.
Gesehen am 28.08.2018